Influence Of Compensation And Career Development On Employee Performance Tasco Minimart - Nurmatin, Fasya Lutfiah; Sutrisna, Arga; Risana, Dudu (Universitas Dehasen Bengkulu, 2023)
The purpose of this study was to determine the effect of compensation and career development on employee performance at TASCO Minimart. The method used by the author in this study is a quantitative approach with sampling techniques using saturated or census samples. The target population in this study were 8 TASCO Minimart outlets with 65 employees in admin, cashier and sales assistant positions. The data analysis technique used is multiple linear regression analysis using SPSS 25. The results show that simultaneously compensation and career development have a significant effect on employee performance. Partially, compensation has no significant effect on employee performance. And partially Career Development has a significant effect on employee performance at TASCO Minimart.